2021
DOI: 10.1080/01650521.2021.1933691
|View full text |Cite
|
Sign up to set email alerts
|

Ravines as conservation strongholds for small wildcats under pressure from free-ranging dogs and cats in Mediterranean landscapes of Chile

Abstract: To analyze the spatial distribution and validate the minimum distance between camera sites, we applied L-function (Besag's transformation of Ripley's K-function). This analysis identifies whether the spatial distribution of the camera sites follows a random, clustered or dispersed process, and identifies the average distance at which the respective process begins. In summary, the algorithm determines when the distribution process of camera sites passes from scattered to clustered considering a theoretical curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 79 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…Our study is coincident with previous records showing the ability of L. guigna to tolerate different landscapes [45,47,50,76], including exotic monocultures and fruit tree plantations (this study). Some of these habitats may be occupied only as hunting or transit sites between areas of dense native vegetation, where permanent refuges and reproductive sites are located.…”
Section: Discussionsupporting
confidence: 92%
“…Our study is coincident with previous records showing the ability of L. guigna to tolerate different landscapes [45,47,50,76], including exotic monocultures and fruit tree plantations (this study). Some of these habitats may be occupied only as hunting or transit sites between areas of dense native vegetation, where permanent refuges and reproductive sites are located.…”
Section: Discussionsupporting
confidence: 92%
“…Figure 7 revealed that only the invasive species could establish when the resource availability was 0.7 kg, contrasting with scenarios where the native species predominated and became the sole prey of the superior predator. Finally, Figure 8 explores the b>1 and c>1 scenario, with a constant body mass of the superior predator (100 kg) and temporal variations in basal resource availability, coexistence between native and invasive species was observed as a resource for the superior predator in the initial 10 seasons, aligning with prior findings (Osorio et al 2021).…”
Section: ₁₆₄supporting
confidence: 79%
“…The definition and description of the variables and parameters are summarized in Table 1. The conceptual model is presented in Figure 4 and is based on an ecological community studied in central-southern Chile by (Osorio et al 2021). The production rates, predation rates, conversion coefficients and all traits present in the model parameters depend on body size and are based on general principles as proposed by metabolic theory (Marquet 2022;Delong 2014).…”
Section: M�������� ��� M������mentioning
confidence: 99%
See 2 more Smart Citations